In situ observation of multiple levels of intermediate chromatin fibers on metaphase chromosomes of Triticum aestivum L. - Wang, Jianyue; Zhang, Feixiong (The Indian Journal of Genetics and Plant Breeding, 2016)
Metaphase chromosomes of root-tip meristematic cells of wheat (Triticum aestivum L.) were carefully examined under the transmission electron microscope. It was obvious that only in one section of a metaphase cell, besides 10 and 25-30 nm fibers, a serial of intermediate chromatin fibers between 30 nm and metaphase chromosome such as 50-60, 100-120 and 200-300 nm, could be identified on three metaphase chromosomes in the cell.The higher degrees of chromatin fibers were helically coiled from the lower levels of chromatin fibers and at last, 750~800 nm metaphase chromosomes were formed from 200-300 nm fibers. It was concluded that the 30 nm chromatin fibers exist truly in the metaphase chromosomes which are hierarchically organized from the 10 nm ones and there are at least 4 levels of helical coils from 30 nm to metaphase chromosomes.